(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the basics of the theory of speech and thinking as the main components of pragmatics. These theories were analyzed on the basis of works written in the direction of psychology, philosophy and Philology. In Kazakh linguistics the interrelation of speech, speech act with thinking is considered for the first time. The article gives specific arguments from the sources about the complex mechanism of thinking and speech, which are peculiar only to man. Communicative situations faced by a person change his / her thinking and speech, along with the change of pragmatic meaning in speech are revealed by the example of oratory discourse. The importance of pragmatism is clearly seen in the analysis of the oratorical discourse. Definitions on types of thinking are given and examples are given. For comparison and understanding of the topic taken from the General concept of the sources of psychology and Philology of the theory of speech. Since pragmatics is considered to be the object of several Sciences, the article was directed and written on the basis of comparison and comparison of the theory of the above Sciences.